PENGGUNAAN ALTERNATIEF DISPUTE RESOLUTION DALAM PENYELESAIAN SENGKETA ANTARA MASYARAKAT DENGAN PEMERINTAH - Suhartono, Slamet (DiH: Jurnal Ilmu Hukum, 2011)
Alternative Dispute Resolution is a method that has many  advantages  compared  with setlement through the judiciary. In addition the process is quick, straight forward, low-cost, and more democratic, this method can also avoid the hostility  between the parties dispute. This method can remove the gap as the government's position is superior to the defendant as the plaintiff's society is moreinferior. Possible for use this method to settle disputes state administration, in asumtif and argumentative based for various reasons, namely the weakness methods of dispute resolution through court institutions, excess Alternative Dispute Resolution methods, the object of disputes, disputes charac-teristic state administration, the doctrine against the law, changes state paradigm, and the enactment of Law Number 30 of l999 on the Arbitrase, Law Number 25 of 2009 on the Public Service, and Law Number 38 of 2007 on Ombudsman.Keywords: dispute between people and government legal protection, alternative dispute resolution